2001
DOI: 10.1034/j.1399-0039.2001.580502.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in RANTES chemokine promoter affects extent of sarcoidosis in a Japanese population

Abstract: RANTES, a member of C-C chemokine, is known to be produced at sites of granulomatous reactions in the lung of sarcoidosis. RANTES is a potent eosinophil and lymphocyte attractant with particular preference for CD45RO+ T cells and eosinophils. Polymorphism of the RANTES promoter has recently been shown to be related to allergic and infectious diseases; atopic dermatitis, asthma, and polymyalgia rheumatica. Considering that this might affect sarcoidosis, we studied polymorphism of the RANTES gene in 114 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…In our The prevalence of the RANTES -403A or -28 G polymorphisms varied among different ethnic groups. The occurrence of the RANTES -403A allele in our study's Korean children was 42.7%, which correlates well with the results for the Japanese (39.3%) [30] and African-Americans (43%) [15]. This level is higher than that of the Chinese (27%) [17], and significantly higher than that of Caucasian ethnic groups (15-20%) [15].…”
Section: Discussionsupporting
confidence: 89%
“…In our The prevalence of the RANTES -403A or -28 G polymorphisms varied among different ethnic groups. The occurrence of the RANTES -403A allele in our study's Korean children was 42.7%, which correlates well with the results for the Japanese (39.3%) [30] and African-Americans (43%) [15]. This level is higher than that of the Chinese (27%) [17], and significantly higher than that of Caucasian ethnic groups (15-20%) [15].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, CCL5 over-production correlates with pulmonary sarcoidosis, particularly in patients with more advanced disease 85 . In agreement with this, Takada et al suggested an association of RANTES-403 G/A polymorphism with the number of organs involved and CD4/ CD8 rate, but not with susceptibility to sarcoidosis as a whole 86 .…”
Section: Lung Diseasesmentioning
confidence: 49%
“…[5][6][7][8][9][10][11][12] Therefore, RANTES could be considered a gene generally predisposing to autoimmune disease. To test this hypothesis, we investigated RANTES SNPs rs2306630, rs2280788 and rs2107538 in a group of 310 CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has not yet been investigated in the context of T1D, although it has been shown to be associated with other autoimmune diseases, such as atopic dermatitis, asthma, sarcoidosis, rheumatoid arthritis and multiple sclerosis. [5][6][7][8][9][10][11][12] RANTES belongs to the family of CC chemokines, which are involved in immunoregulatory and inflammatory processes owing to their ability to recruit, activate and co-stimulate T cells and monocytes. 13,14 In addition to the trafficking effect, RANTES, like other CC chemokines, plays an important role in co-stimulation of T-cell proliferation 15,16 and activation of the T cells localized in the inflammatory lesion.…”
Section: Introductionmentioning
confidence: 99%